Changes in Healthcare Utilization After the 2022 Seoul Metropolitan Flood: Applying a Generalized Synthetic Control Approach - Marnpyung Jang; Jaeyoung Yoon; Yeseul Yun; Jaiyong Kim; Hoyeon Jang; Tarik Benmarhnia; Changwoo Han (GeoHealth)
Abstract Floods can have adverse health effects and impose a burden on healthcare systems. However, the potential consequences of floods on specific medical causes in densely populated metropolitan cities has not been characterized yet. Therefore, we evaluate the changes in healthcare utilization patterns after the 2022 Seoul flood using nationwide health insurance data. Based on the flood inundation map, districts within the flooded municipalities of Seoul were classified as severe‐(n = 12), mild‐(n = 22), or non‐(n = 38) flood‐affected districts. Capitalizing on the timing of the flood as a natural experiment, a generalized synthetic control method was applied to estimate changes in the number of disease‐specific hospital visits in flood‐affected districts during 2 weeks after the flood. We found excess hospital visits for external injuries (20.2 visits, 95% CI: −6.0, 45.2) and fewer visits for pregnancy and puerperium (−3.0 visits, 95% CI: −5.1, −0.5) in residents of flooded districts. When comparing severe‐ and non‐flood districts, the increase in hospital visits for external injuries (56.2 visits, 95% CI: 17.2, 93.2) and a decrease in hospital visits related to pregnancy and puerperium (−5.3 visits, 95% CI: −8.4, −1.6) were prominent in residents living in severe‐flood affected districts. Disease specific analysis showed an increase in hospital visits for injuries to the elbow and forearm, ankle and foot injuries, and chronic lower respiratory diseases in severe‐flood‐affected districts. However, these impacts were not observed when comparing the mild‐ and non‐flood‐affected districts. Our study suggests an immediate and substantial change in medical demand following flood exposure, highlighting the importance of public health responses after flood events.